Mitochondrial SLC25 Carriers: Novel Targets for Cancer Therapy - Rochette, Luc; Meloux, Alexandre; Zeller, Marianne; Malka, Gabriel; Cottin, Yves; Vergely, Catherine (Molecules (Basel, Switzerland), 2020)
The transfer of metabolites through the mitochondrial membranes is a vital process that is highly controlled and regulated by the inner membrane. A variety of metabolites, nucleotides, and cofactors are transported across the inner mitochondrial membrane (IMM) by a superfamily of membrane transporters which are known as the mitochondrial carrier family (MCF) or the solute carrier family 25 (SLC25 protein family). In humans, the MCF has 53 members encoded by nuclear genes. Members of the SLC25 family of transporters, which is the largest group of solute carriers, are also known as mitochondrial carriers (MCs). Because MCs are nuclear-coded proteins, they must be imported into the IMM. When compared with normal cells, the mitochondria of cancer cells exhibit significantly increased transmembrane potentials and a number of their transporters are altered. SLC25 members were identified as potential biomarkers for various cancers. The objective of this review is to summarize what is currently known about the involvement of mitochondrial SLC25 carriers in associated diseases. This review suggests that the SLC25 family could be used for the development of novel points of attack for targeted cancer therapy.